2010
DOI: 10.1126/science.1183621
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Transcription Factor Binding Among Humans

Abstract: Differences in gene expression may play a major role in speciation and phenotypic diversity. We examined genome-wide differences in transcription factor (TF) binding in several humans and a single chimpanzee using chromatin immunoprecipitation followed by sequencing (ChIP-Seq). The binding sites of RNA Polymerase II (PolII) and a key regulator of immune responses, NFκB (p65), were mapped in ten lymphoblastoid cell lines and 25% and 7.5% of the respective binding regions were found to differ between individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
382
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 520 publications
(419 citation statements)
references
References 19 publications
29
382
1
3
Order By: Relevance
“…The NF-B family of transcription factors consists of five proteins, namely, RelA (p65), RelB, c-Rel, NF-B1 (p50/p105), and NF-B2 (p52/p100) (13). Kasowski and colleagues performed chromatin precipitation followed by deep sequencing to look at genome-wide binding of p65 protein in human lymphoblastoid cells (17). We took advantage of these data and manually inspected the presence of p65 on tRNA genes using the ENCODE transcription factor ChIP track in the UCSC genome browser (http://genome.ucsc.edu) (32,33).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NF-B family of transcription factors consists of five proteins, namely, RelA (p65), RelB, c-Rel, NF-B1 (p50/p105), and NF-B2 (p52/p100) (13). Kasowski and colleagues performed chromatin precipitation followed by deep sequencing to look at genome-wide binding of p65 protein in human lymphoblastoid cells (17). We took advantage of these data and manually inspected the presence of p65 on tRNA genes using the ENCODE transcription factor ChIP track in the UCSC genome browser (http://genome.ucsc.edu) (32,33).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, elevated Pol III activity is a recurring feature of mouse and human tumors (14). Interestingly, NF-B subunit RelA/p65 has been shown to associate with Pol III-transcribed genes in human lymphoblastoid cells (17). However, its role in Pol III transcriptional regulation has not yet been determined.…”
mentioning
confidence: 99%
“…Individuals of the same species also display considerable variation albeit at lower levels, as expected. Comparison of 10 human individuals revealed a higher fraction of shared events, but as low as 75% in the case of RNA polymerase II (Pol II) [23]. Similarly, when comparing two Saccharomyces cerevisiae strains, around 70% of the genes putatively bound by Ste12 were found to be conserved [25].…”
Section: Using Chromatin Immunoprecipitation To Study Genome-wide Enhmentioning
confidence: 99%
“…Analysis of ChIP-seq data [26] revealed that the SNP was located within an NF-KB target site in LCLs ( Figure 6A) and contained an NF-KB consensus binding motif. We investigated whether the A to G substitution could modulate predicted binding affinity using a publically available database identifying binding sites of NF-KB by a combination of protein-binding microarrays and surface plasmon resonance [27].…”
Section: Insights From the Genetical Genomics Of Ciitamentioning
confidence: 99%
“…We then proceeded to determine whether allelic differences in NF-KB binding were present ex vivo using ChIP-seq data for a panel of five LCLs heterozygous for rs11074938 [26]. This revealed that there was significantly more RELA binding to the A allele compared to the G, with on average 66.1% (SD 8.1) of reads mapping to the A allele (P =0.008) ( Figure 6C).…”
Section: Insights From the Genetical Genomics Of Ciitamentioning
confidence: 99%